CARcinogen EXposure: CAREX - Yari, Saeed; Fallah Asadi, Ayda; Mosavi Jarrahi, Alireza; Nourmohammadi, Mohammad (Asian Pacific Journal of Environment and Cancer, 2018)
Cancer is the second common cause of death worldwide and a significant ratio of all cancers is related to occupational and living environments. On the other side, cancer prevalence could be controlled and prevented via policies to improve occupational and living environments. However, a main challenge in prevention of occupational cancer is the lack of knowledge about the exposure rate and number of exposed persons. CAREX database, which is established by the program of Europe against cancer, provides information for the number of exposed persons based on country, carcinogen, and type of industry. CAREX is established in early years of 1990 decade by Finland Institute of Health (FIOH) in cooperation with IARC and European experts, as a tool for estimation of the burden due to occupational cancer in Europe, and shortly thereafter is expanded for use in almost 15 countries in European Union by 55 industrial groups. Several other countries have used CAREX for their countries and have provided some main progressions for the performance model. CAREX project in Canada was modeled in 2007, in an effort to develop a Canadian specific and advanced tool for assessing exposure to carcinogenic agents based on EU CAREX. In this model, not only occupational exposure, but also environmental exposure has been considered. Estimation of exposure with CAREX helps to inform primary prevention activities and to improve global occupational cancer, and its strength points are systematic nature, good coverage and ease of use, and can be used in other countries of the world.